Eco-Theology in the Social Construction of Santri: Values and Clean-Living Practices in Islamic Boarding Schools - Khairul Umam; Abdul Karim; Moh. Dasuki (Fenomena, 2024)
Hygiene and environmental management issues have a significant impact on public health, especially in boarding schools such as Islamic boarding schools, where access to sanitation facilities and clean water is often limited. Previous studies have examined hygiene practices and environmental education in general; however, there remains a lack of understanding of how theological and socio-cultural values are constructed to shape students' ecological awareness. This study aims to examine the social construction of ecological theology at the Nurul Qornain Islamic Boarding School, focusing on how hygiene values are internalized, objectified through rules and routines, and manifested in the ecological habitus of students. The study employed a qualitative case study approach, utilizing purposive sampling techniques to select key informants, including clerics, administrators, teachers, and students. Data were obtained through in-depth interviews, participatory observation, and document analysis, then analyzed using thematic coding and triangulation techniques. The results of the study demonstrate that cleanliness is understood not merely as a physical activity, but as a spiritual obligation and manifestation of servitude to Allah, which is conveyed through formal education, the hidden curriculum, and daily practices. This study confirms that Islamic boarding schools are dynamic spaces for fostering ecological awareness rooted in religious values. Permasalahan kebersihan dan pengelolaan lingkungan memiliki dampak signifikan terhadap kesehatan masyarakat, terutama di lembaga berasrama seperti pesantren, di mana akses terhadap fasilitas sanitasi dan air bersih sering terbatas. Studi sebelumnya telah meneliti praktik kebersihan dan pendidikan lingkungan secara umum, namun masih terdapat kekurangan pemahaman mengenai bagaimana nilai-nilai teologi dan budaya sosial dikonstruksi untuk membentuk kesadaran ekologis santri. Penelitian ini bertujuan untuk mengkaji konstruksi sosial teologi ekologi di Pondok Pesantren Nurul Qornain, dengan fokus pada bagaimana nilai kebersihan diinternalisasi, diobjektivasikan melalui aturan dan rutinitas, serta diwujudkan dalam habitus ekologis santri. Penelitian menggunakan pendekatan studi kasus kualitatif dengan teknik purposive sampling untuk memilih informan kunci, termasuk kiai, pengurus, ustadz, dan santri. Data diperoleh melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, kemudian dianalisis dengan teknik coding tematik dan triangulasi. Hasil penelitian menunjukkan bahwa kebersihan dipahami bukan sekadar aktivitas fisik, tetapi sebagai kewajiban spiritual dan manifestasi penghambaan kepada Allah, yang diterapkan melalui pendidikan formal, hidden curriculum, dan praktik sehari-hari. Studi ini menegaskan bahwa pesantren menjadi ruang dinamis untuk membangun kesadaran ekologis berbasis nilai religius.